Mortality and prognostic factors in connective tissue disease‐associated pulmonary arterial hypertension patients complicated with right heart failure. (9th March 2023) - Deng, Xiaoyue; Jiang, Nan; Huang, Can; Zhou, Shuang; Peng, Linyi; Zhang, Li; Liu, Jinjing; Wang, Li; Zhou, Jiaxin; Wang, Qian; Weng, Li; Peng, Jinmin; et al.
Abstract: Objective: To identify predictive factors associated with mortality in connective tissue disease‐associated pulmonary arterial hypertension (CTD‐PAH) patients who were complicated with right heart failure (RHF). Methods: In this single‐center retrospective study, baseline demographics, clinical features, laboratory results, and hemodynamic assessments were collected. Kaplan–Meier analysis was applied to analyze all‐cause mortality. Univariate and forward stepwise multivariate Cox proportional regression analyses were performed to identify independent predictors of mortality. Results: A total of 51 right heart catheterization‐confirmed CTD‐PAH patients complicated with RHF were consecutively enrolled in this study from 2012 to 2022. Forty‐eight (94%) enrolled patients were female and the mean age was 36.0 ± 11.8 years. Thirty‐two (61.5%) were systemic lupus erythematosus‐PAH and 33%/67% showed World Health Organization functional class III/IV, respectively. Twenty‐five (49%) of those patients died and Kaplan–Meier analysis showed the overall 1‐, 3‐, and 5‐week survival rates from the time of hospitalization as 86.28%, 60.78%, and 56.86%, respectively. RHF in CTD‐PAH patients mainly resulted from progression of PAH ( n  = 19) and infection ( n  = 5), which also contributed to the leading causes of death. Statistical analysis between survivors and non‐survivors showed that death from RHF was associated with higher levels of urea (9.66 vs 6.34 mmol/L, P  = 0.002), lactate (cLac: 2.65 vs 1.9 mmol/L, P  = 0.006), total bilirubin (23.1 vs 16.9 μmol/L, P  = 0.018) and direct bilirubin (10.5 vs 6.5 μmol/L, P  = 0.004), but with lower levels of hematocrit (33.7 vs 39, P  = 0.004), cNa+ (131 vs 136 mmol/L, P  = 0.003). Univariate and forward stepwise multivariate Cox proportional regression analyses indicated that the level of cLac (hazards ratio:1.297; 95% CI: 1.076–1.564; P  = 0.006) was an independent risk factor for mortality. Conclusion: The short‐term prognosis of CTD‐PAH complicated with RHF was very poor, and hyperlactic acidemia (cLac > 2.85 mmoL/L) was an independent predicting factor for mortality of CTD‐PAH patients complicated with RHF.